Cardiac arrest and related mortality in emergency departments in the United States: Analysis of the nationwide emergency department sample. (December 2020) - Ravindran, Roshini; Kwok, Chun Shing; Wong, Chun Wai; Siller-Matula, Jolanta M.; Parwani, Purvi; Velagapudi, Poonam; Fischman, David L.; Alraies, Chadi; Michos, Erin D.; Mamas, Mamas A.
Abstract: Aims: The aim of this study is to analyse the causes of cardiac arrests (CA) in the emergency departments (ED) in the United States and their clinical outcomes according to whether they had a primary or a secondary diagnosis of CA. Methods: Data from the Nationwide Emergency Department Sample was assessed for episodes of CA in the emergency department (ED) for adults from 2006 to 2014. Primary and secondary diagnoses of CA and mortality outcomes were evaluated in ED, inpatient and the combined in-hospital setting. Results: There were 2, 852, 347 ED episodes with a diagnosis of CA (50.5% primary diagnosis, 49.5% secondary diagnosis). Among patients with a secondary diagnosis of CA, ∼33% patients had a primary cardiac diagnosis, followed by infectious and respiratory diagnoses. The survival to ED discharge was 53.2%; lower for primary versus secondary CA diagnosis (20.4% vs 86.7%). The in-hospital survival rate for all CA was 28.7%, and was lower for primary versus secondary CA diagnosis (15.7% vs 41.9%). Survival to hospital discharge was highest in the age group of 41–60 years (33.0%) and was least among >80 years (20.9%). Survival was also noted to be lower among female patients (27.9% vs 29.2%) and in the winter months. Conclusions: Survival with CA in ED is <30% of patients and is greater among patients with a secondary diagnosis of CA. CAs are associated with significant mortality in ED and hospital settings and measures should be taken to better manage cardiac, infection and respiratory causes particularly in the winter months.